Norway : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2014)
This Selected Issues paper examines migration patterns in Norway and their implications for estimates of potential output. It applies a new methodology proposed by Borio and others (2013) to estimate potential output by drawing on information about immigration and oil price movements. The paper also provides an overview of the recent trend in immigration in Norway and discusses various estimates of potential output using standard approaches. The results indicate that immigration plays a small but statistically significant role in the estimation of potential output for Norway. The data show that immigration inflows into Norway vary across source countries. The largest share of immigrants is from Poland, accounting for 15 percent of the total in 2012. Immigration patterns in Norway contain both cyclical and structural elements, but the latter seems dominant at least for now. Empirical results also suggest that immigration plays some role in determining potential output, however, its impact is quite small, consistent with the view that the recent immigration patterns are structural.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet